IDENTIFIKASI KUALITAS CADANGAN AIR TANAH DI KECAMATAN SEKARAN KABUPATEN LAMONGAN - Rifko Harny Dwi Cahyo; Irasani Rahayu (Jurnal Matematika dan Sains (JMS), 2023)
Groundwater is part of the hydrological cycle located below the earth's surface in the pores and crevices of rocks and soil. Water scarcity is increasing around the world and the need for water presence is increasing due to growing demands in several fields. Geologically, Sekaran District is composed of alluvium formations where this formation consists of kerakal, gravel, silt sand, clay, local fragments of fossil shells and mud. This study was conducted to determine the quality of groundwater reserves based on the value of solute solids. The method carried out by taking water samples in the wells of residents' houses in Sekaran District.After data processing was carried out, it was found that the quality of groundwater reserves based on the value of dissolved materials in Sekaran District ranged from 50-950 ppm and based on electrical conductivity values ranging from 100-2000 ?S/cm.